Does shoulder impingement syndrome affect the shoulder kinematics and associated muscle activity in archers? - Shinohara, H.; Urabe, Y.; Maeda, N.; Xie, D.; Sasadai, J.; Fujii, E. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: Archery related injuries, such as shoulder impingement syndrome are caused by repeated motion of the shoulder. The aim of this study was to analyze differences in the shoulder kinematics and the associated muscle activity between archers with shoulder impingement and uninjured archery players.